2021
DOI: 10.1186/s13071-021-04979-w
|View full text |Cite
|
Sign up to set email alerts
|

First report of interspecific transmission of sarcoptic mange from Iberian ibex to wild boar

Abstract: Background Sarcoptic mange is a globally distributed parasitic disease caused by the burrowing mite Sarcoptes scabiei. This mite has a certain degree of host specificity, although interspecific transmission can occur among phylogenetically related species or through prey–predator mediated exposure. In 2018, a wild boar (Sus scrofa) with lesions compatible with sarcoptic mange was hunted in Ports de Tortosa i Beseit Natural Park (PTB, north-eastern Spain), where an active epizootic outbreak of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 67 publications
2
12
0
Order By: Relevance
“…The rapid drop of plasma IVM concentration in Iberian ibex after a single oral dose found in this study, and the lack of published results on therapeutic trials with oral IVM in scabietic free-ranging individuals suggest caution in promoting the mass delivery of IVM medicated pellets as a measure to efficiently control sarcoptic mange at the individual and population level in this wild caprine. The epidemiological effects of partially ineffective treatment strategies could even be opposite, by lengthening the infective stage of the individuals affected by sarcoptic mange and therefore increasing the dissemination and spread of the disease (25), potentially to other mammal species too (12,49). Moreover, aspects such as the proportion of the target population actually receiving the treatment, the access to the drug by non-target species, and the environmental effects of the massive release of IVM in the environment, are still in need to be thoroughly investigated and controlled (8,10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rapid drop of plasma IVM concentration in Iberian ibex after a single oral dose found in this study, and the lack of published results on therapeutic trials with oral IVM in scabietic free-ranging individuals suggest caution in promoting the mass delivery of IVM medicated pellets as a measure to efficiently control sarcoptic mange at the individual and population level in this wild caprine. The epidemiological effects of partially ineffective treatment strategies could even be opposite, by lengthening the infective stage of the individuals affected by sarcoptic mange and therefore increasing the dissemination and spread of the disease (25), potentially to other mammal species too (12,49). Moreover, aspects such as the proportion of the target population actually receiving the treatment, the access to the drug by non-target species, and the environmental effects of the massive release of IVM in the environment, are still in need to be thoroughly investigated and controlled (8,10).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, no studies support the actual effectiveness of this common practice. In fact, essential gaps in knowledge need to be filled before considering oral mass treatments as a possible control measure for the management of sarcoptic mange in free-ranging Iberian ibex and other susceptible wild ruminants (11,12). Among the knowledge gaps to fill before implementing any in-field treatment, the pharmacokinetics of orallyadministered candidate acaricides in the target hosts are crucial.…”
Section: Introductionmentioning
confidence: 99%
“…Dwużnik et al [ 11 ] advanced the hypothesis of a mechanism generated by the host-hyperimmune response during the first days after the tick attachment, leading to a deep penetration of the hypostome through the hypodermic layers, and its progressive embedment (also called “sinking”) underneath the skin, impeding it to resurface. As already shown for other ectoparasites, such as the mite Sarcoptes scabiei causing sarcoptic mange, different host species can have different immune responses [ 29 , 30 , 31 , 32 ] with various degrees of clinical signs depending on the age, sex, and body condition, as it may happen with ticks. In particular, red foxes would be less effective at countering sarcoptic mange (frequently showing severe skin lesions) due to a lack of memory T-cells after the contact with Sarcoptes mites [ 29 , 33 ], which might also explain the higher incidence of SCT in this species.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the literature, the authors have personal experience that ZS is not uncommon among hunters and gamekeepers in areas of Central and Southern Europe where mountain-dwelling ruminants are endemically infected with sarcoptic mange [44,47]. However, to the authors' knowledge, no ZS cases have been reported in wild boar hunters, although the disease is observed in wild boar throughout Europe [13,64,65]. Delafond and Bourguignon [7] mention a single ZS case following contact with the skin of a scabietic wild boar in Germany.…”
Section: Overview Of Zoonotic Scabies Episodesmentioning
confidence: 90%
“…Transmission from humans to animals has also been documented in mountain gorillas [11]. Furthermore, S. scabiei cross-transmission between different animal species has been reported in more than 50 species [12,13], under natural or human-driven conditions, highlighting the pronounced epidemiological plasticity of this ectoparasite.…”
Section: Introductionmentioning
confidence: 99%